The theoretical evaluation of the poly(3,4-dimetylpyrroIe) cathodic electrodeposition assisted by manganate ions - Романів, Людмила Вікторівна (Vietnam Journal of Chemistry, 2018)
The theoretical description of poly(3,4-dimethylpyrrole) cathodic electrodeposition in alkaline media has been reported for the first time. The electrochemical deposition of conducting polymer on cathode is realized by in situ formation of manganate-ions (MnO42-) as oxidizing agents, and the proper polymer may be doped by hypomanagate, ions (MnO43-). The stable steady-state in this system was established rapidly and efficiently, and the polymer surface has to be well developed. No electrochemical instabilities, typical for anodic direct electropolymerization, was observed.
Keywords: Conducting polymers, polypyrrole, cathodic electrodeposition, manganate ions, stable steady-state.